The clearance crisis and its impact on the GDP in Palestine between the years (1997-2019) - Sawafta, Othman Ahmed; Atili, Mohammed Rabhi (Journal of Economic, Administrative and Legal Sciences, 2021)
This study aimed to analyze the revenue of clearance tax in Palestine between the years (1997-2019), and to demonstrate the impact of the clearance tax crisis on the gross domestic product in Palestine. The study relied on the descriptive and analytical approach. And used the statistical analysis program STATA and SPSS 23, the study found that there is an effect of clearance revenues on GDP, and that an increase in one unit in clearing revenues leads to an increase of 4.319 unit in GDP, and that there are no statistically significant differences in GDP between the years that a crisis occurred and the years in which there was no crisis attributed to the clearance tax, and the study recommended reformulating economic understandings with Israel, the most important of which is the Paris Economic Protocol, and try to separate economically from Israel and push for the independence of the Palestinian economy, and reducing reliance on clearance tax revenues in financing the general budget due to the control of the Israeli occupation using it as a means of pressure on the Palestinian Authority.
Keywords: clearance crisis; revenues; Paris Economic Agreement